Impact of general and central adiposity on ventricular-arterial aging in women and men - Wohlfahrt, Peter; Redfield, Margaret M; Lopez-Jimenez, Francisco; Melenovsky, Vojtech; Kane, Garvan C; Rodeheffer, Richard J; Borlaug, Barry A (JACC. Heart failure, 2014)
OBJECTIVES: The aim of this study was to assess the effects of central and general obesity measures on long-term longitudinal changes in ventricular-arterial mechanics. BACKGROUND: Obesity, female sex, and ventricular-arterial stiffening are associated with the development of heart failure with preserved ejection fraction. Fat distribution and chronic changes in body composition may affect longitudinal changes in LV properties, independent of arterial load. METHODS: In 1,402 subjects from a randomly selected, community-based population, comprehensive echo-Doppler echocardiography was performed at two examinations separated by 4 years. From this population, 788 subjects had paired data adequate for determining left ventricular end-systolic elastance (Ees), end-diastolic elastance (Eed), and effective arterial elastance (Ea). RESULTS: Over 4 years, Ea was decreased by 3% in tandem with improved blood pressure control, whereas Ees and Eed were increased by 14% and 8% (all, p < 0.001). Greater weight loss over 4 years was associated with progressively greater decreases in Ea in men and women. After adjustment for Ea change, weight gain was correlated with increases in Eed in both women and men. Central obesity was associated with greater age-related increases in Ees in women but not in men, independent of arterial load, but central obesity did not predict changes in Eed or Ea. CONCLUSIONS: In these subjects, weight gain was associated with increases in LV diastolic stiffness, even after adjustment for changes in arterial afterload, whereas weight loss was associated with reductions in arterial stiffness. Age-related LV systolic stiffening was increased in women, but not in men, with central obesity. Strategies for promoting weight loss and reducing central adiposity may be effective in preventing heart failure with preserved ejection fraction, particularly in women.
Keywords: Obesity, Abdominal; Female; Heart Ventricles; vascular stiffness; ženské pohlaví; srdeční komory; Aging; longitudinální studie; Obesity; funkce levé komory srdeční; Elasticity; pružnost; lidé; dopplerovská echokardiografie; tuhost cévní stěny; heart failure; Echocardiography, Doppler; Sex Factors; obezita; Male; Aged; sexuální faktory; stárnutí; ventricular stiffness; lidé středního věku; senioři; mužské pohlaví; abdominální obezita; Vascular Stiffness; obesity; Middle Aged; Longitudinal Studies; Ventricular Function, Left; aging; Humans